Establishing an indwelling peritoneal catheter as a standard procedure for hospitalized patients with ascites: Retrospective data on feasibility, effectiveness and safety. Issue 5 (1st June 2019) - Stratmann, Katharina; Fitting, Daniel; Zeuzem, Stefan; Bojunga, Jörg; Trebicka, Jonel; Friedrich-Rust, Mireen; Dultz, Georg
Abstract : Background: The use of an indwelling peritoneal catheter system in hospitalized patients with ascites could facilitate patient management by the prevention of repetitive abdominal paracentesis. Despite these possible benefits, the use of indwelling catheters is not widely established. Objective: This retrospective study aimed to evaluate the feasibility, effectiveness and safety of the use of an indwelling catheter for ascites drainage in the clinical routine. Methods: This retrospective study included all indwelling peritoneal catheter placements in our department in hospitalized patients with cirrhosis between 2014 and 2017. Results: A total of 324 indwelling catheter placements for ascites in 192 hospitalized patients with cirrhosis were included. The catheter (7F, 8 cm) was placed ultrasound‐assisted bed‐side on the hospital ward. The technical success rate of the catheter placement was 99.7% (323/324). In 17.5% (64/324) the catheter was placed to optimize ascitic drainage prior to an abdominal intervention (e.g. transjugular intrahepatic portosystemic shunt). The median time of catheter retention was 48 hours (8–168 hours) and the median cumulative amount of drained ascites 8000 ml (550–28, 000). The most common adverse event was acute kidney injury (49/324, 15.1%); the risk was particularly higher in patients with a Model for End‐Stage Liver Disease (MELD) score ≥ 16 ( p  = 0.028; odds ratio 2.039). Ascitic fistula after catheter removal was observed in 9.6% (31/324). Catheter‐related infections occurred in 4.3% (14/324), and bleeding was documented in three cases (0.8%) with one major bleeding (0.3%). Conclusion: The placement of an indwelling catheter for repetitive ascitic drainage in hospitalized patients with cirrhosis can be established in the clinical routine, facilitating patient management. High‐MELD patients especially have to be monitored for acute kidney injury.